Toll-like receptor-4 signaling drives persistent fibroblast activation and prevents fibrosis resolution in scleroderma - Bhattacharyya, S; Midwood, K; Yin, H; Varga, J (Mary Ann Liebert, Inc., 2017)
Significance: This review provides current overview of the emerging role of innate immunity in driving fibrosis, and preventing its resolution, in scleroderma (systemic sclerosis, SSc). Understanding the mechanisms of dysregulated innate immunity in fibrosis and SSc will provide opportunities for therapeutic interventions using novel agents and repurposed existing drugs. Recent Advances: New insights from genomic and genetic studies implicate components of innate immune signaling such as pattern recognition receptors (PRRs), downstream signaling intermediates, and endogenous inhibitors, in fibrosis in SSc. Recent studies distinguish innate immune signaling in tissue-resident myofibroblasts and bone marrow-derived immune cells and define their roles in the development and persistence of tissue fibrosis. Critical Issues: Activation of toll-like receptors (TLRs) and other PRR mechanisms occurs in resident nonimmune cells within injured tissue microenvironments. These cells respond to damage-associated molecular patterns (DAMPs), such as tenascin-C that are recognized as danger signals, and elicit matrix production, cytokine secretion, and myofibroblast transformation and survival. When these responses persist due to constitutive TLR activation or impaired termination by endogenous inhibitors, they interfere with fibrosis resolution. The genetic basis and molecular mechanisms of these phenomena in the context of fibrosis are under current investigation. Future Directions: Precise delineation of the pathogenic DAMPs, their interaction with TLRs and other PRRs, the downstream signaling pathways and transcriptional events, and the fibroblast-specific regulation and function of endogenous inhibitors of innate immunity, will form the foundation for innovative targeted therapies to block fibrosis by reestablishing balanced innate immune signaling in fibroblasts.